PERAN MAHASISWA PPL FEBI UIN SAIZU DALAM MEMBANTU MENINGKATKAN PENJUALAN PADA UMKM AL-MUNA BAKERY - Umdah Aulia Rohmah; Himayatul Hidayat Nur; Diva Nur Apriliani; Lulu Khulwatu Iffah; Estri Nuraini Hidami (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The most economic activity carried out by the indonesian people is Micro, Small and Medium Enterprises (MSMEs). MSMEs are known for their relativelly easy to develop types of businesses with vaious creations and innovations and have crucial potential in driving the economy in Indonesia. The existance of MSMEs can reduce poverty and unemployment in Indonesia. In addition, MSMEs have the potential to compete on the national and even international stage if they continue to be encouraged with innovation and creation that follows the times. If this can be realized, of course it can help increase economic income and community welfare can be fulfilled. In this trudy, PPL FEBI UIN SAIZU Purwokerto students helped MSMEs in Banyumas, namely the Al-Muna Bakery MSME. PPL students helped with production, offline promotion, online promotion of financial reports, adna others. The research was conducted using a qualitative method, descrtiptive analysis method with direct observation and interviews. The result of this study show that the role of students is very important in helping to encourge MSME businesses, especially in terms of increasing sales turnover.